2016
DOI: 10.1038/bmt.2016.264
|View full text |Cite
|
Sign up to set email alerts
|

ABO incompatibility does not influence transfusion requirements in patients undergoing single-unit umbilical cord blood transplantation

Abstract: Hematopoietic stem cell transplantation is usually performed without considering the ABO compatibility between donor and recipient. There are few studies analyzing ABO matching impact on transfusion outcome of umbilical cord blood transplantation (UCBT) recipients. The aim of this study was to analyze factors influencing transfusion outcome, highlighting the ABO matching between donor and recipient. This study has reviewed data from 318 patients who underwent single unit UCBT at la Fe University Hospital from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
3
10
2
Order By: Relevance
“…Not surprisingly, major ABO incompatibility was associated with significantly increased RBC transfusions during both time periods. This association has been frequently, but not consistently, observed in studies of recipients of other types of allo‐HSCTs …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Not surprisingly, major ABO incompatibility was associated with significantly increased RBC transfusions during both time periods. This association has been frequently, but not consistently, observed in studies of recipients of other types of allo‐HSCTs …”
Section: Discussionmentioning
confidence: 86%
“…The median number of days to achieve RBC and platelet transfusion independence were 34 days (95% confidence interval, or 95% CI: [28][29][30][31][32][33][34][35][36][37][38][39][40] independence, and 89.5% (95% CI: 83.5%-93.4%) had achieved platelet independence ( Table 2, and Fig. 1A and B).…”
Section: Transfusion Independencementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to these reports on patients receiving reduced intensity regimens, a study where 93% of the patients underwent auto‐HSCT after a myeloablative regimen reported that 90% required transfusion support 23 . The lower transfusion support demand with RIC versus myeloablative conditioning regimens has been well documented previously 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…UCBT procedures including conditioning regimes, GVDH prophylaxis, and supportive care have been previously reported. 4,12 For haplo-HSCT, G-CSF mobilized peripheral blood stem cells were used as graft source, without further manipulation. The conditioning regimen consisted of either a conventional myeloablative regimen (MAC) or a reduced intensity conditioning (RIC) for patients unfit to receive MAC.…”
Section: Patientsmentioning
confidence: 99%